SIFAT FISIS DAN PENGERINGAN LIMA JENIS BAMBU - Efrida Basri; Rohmah Pari (Jurnal Penelitian Hasil Hutan, 2017)
Information regarding physical properties of bamboo is essential for interpreting its dimensional stability, while drying properties are needed as a basis in determining the optimum drying temperature. This research was aimed to investigate the effect of bamboo species and position at the culm on physical properties, as well as drying properties of five bamboo species i.e. temen bamboo (Gigantochloa verticillata Munro), ori (Bambusa blumeana Bl. ex Schult.f.), ater (Gigantochloa atter (Hassk.) Kurz ex Munro), ampel (Bambusa vulgaris Schrad.), and peting (Gigantochloa levis (Blanco) Merr.). Physical properties were tested by measuring diameter and thickness of bamboo culms. Determination of drying temperature was carried out in accordance with wood drying method and followed by observing visual defects, i.e. deformation (concave & wrinkle) and end/node split. Assessment results revealed that there were close relationships between green moisture content of bamboo and their density as well as their culm shrinkage. Based on bamboo drying properties (bottom-middle portions), the optimum drying temperatures (initial and final temperature) for temen and ori were occurred at 45 – 70°C, ampel and ater were occurred at 40 – 60°C, while the optimum drying temperature for peting were at 33 – 50°C